Involvement of lncRNAs and Macrophages: Potential Regulatory Link to Angiogenesis - Yang Jia; Yedi Zhou (Journal of Immunology Research)
Macrophages are involved in angiogenesis, an essential process for organ growth and tissue repair, and could contribute to the pathogenesis of angiogenesis-related diseases such as malignant tumors and diabetic retinopathy. Recently, long noncoding RNAs (lncRNAs) have been proved to be important in cell differentiation, organismal development, and various diseases of pathological angiogenesis. Moreover, it has been indicated that numerous lncRNAs exhibit different functions in macrophage infiltration and polarization and regulate the secretion of inflammatory cytokines released by macrophages. Therefore, the focus of macrophage-related lncRNAs could be considered to be a potential method in therapeutic targeting angiogenesis-related diseases. This review mainly summarizes the roles played by lncRNAs which associated with macrophages in angiogenesis. The possible mechanisms of the regulatory link between lncRNAs and macrophages in various angiogenesis-related diseases were also discussed.